Development of asymmetric polyethersulfone hollow fiber ultrafiltration membrane for cyclodextrin separation - Mustaffar, Mohd. Idham (2004)
The main objective of this research is to develop asymmetric polyethersulfone hollow fiber ultrafiltration (UF) membrane for enzyme (cyclodextrin) separation. Manipulation of rheological and phase inversion factors, including polymer concentration, solvent ratio, forced-convective evaporation time and shear rate during fiber spinning provided a potential platform to develop asymmetric hollow fiber membranes with superior separation performance. Therefore, the present research was conducted to investigate the effects of the selected fabrication parameters such as polymer concentration, dope extrusion rate (DER) and type of bore fluid on membrane properties and structures. For the first stage of study, three different types of polymer solution which consists of polyethersulfone, 1-methyl-2-pyrrolidone, polyethylene glycol and distilled water had been developed by using turbidimetric titration method. These polymer solutions were specifically designed to be very close to its cloud point (binodal line) in order to accelerate the coagulation of nascent fibers which reduced the relaxation effect on molecular orientation. At the second stage, the effect of bore fluid on the performance of membrane spun from optimized polymer solution was investigated. Distilled water and a mixture of potassium acetate and distilled water with a different level of water activity were employed. The results showed that the membrane spun using the mixture of potassium acetate and water achieved better performance in terms of flux and rejection as compared to using water as bore fluid. Therefore, the bore fluid of potassium acetate/water (low water activity) was used for the later phase of experiment. In the next stage, the effect of polymer concentration on membrane performance was studied. The three new developed polymer solutions were used in this study. The results revealed that the flux of hollow fiber ultrafiltration membrane decreases while the rejection for particle solute increases with an increase in polymer concentration. At the last stage of the study, the effect of dope extrusion rate on the performance of membrane spun from optimized polymer solution was investigated. The hollow fiber membrane was spun at five different DER. The results suggested that there were optimum conditions at certain DER which yields an optimal performance of cyclodextrin rejection. Once the separation performance reaches maximum (critical point), the rejection decreases with increasing dope extrusion rate. The membrane structure was further characterized by using scanning electron microscopy (SEM) and plane polarized infra-red Fourier transform spectroscopy to investigate the structure and morphology of membranes and to directly measure the molecular orientation on membrane active layer, respectively. As a conclusion, the combination of low water activity bore fluid, polymer concentration of 18.5 wt.% and dope extrusion rate of 3.5 cm3/min has been identified as the most favorable conditions to produce high performance hollow fiber UF membrane for cyclodextrin separation. At this condition, the rejection of ultrafiltration membrane for cyclodextrin separation is about 99.51% with the flux of about 0.47 L/m2.h.